The Phenomenon of Anomie in the Context of Marginality - Hakobyan, Naira; Dabaghyan, Artak; Khachatryan, Anna (ՀՀ ԳԱԱ)
It’s difficult to imagine any social community without marginal phenomena – marginal groups, people, social roles, displays of marginal consciousness and behavior. In every society individuals, social and ethnic groups and social strata act as bearers of marginal qualities. In other words, marginality is a social-cultural and social-psychological phenomenon, which has always been an indivisible part of different historical societies of various social types. In this sense, the study of the phenomenon of anomie, considered in the context of marginality, is especially important. The importance of problems of anomic identities increases especially in transforming societies, where in the result of political, economic, social and cultural reconstructions oncestable social structures are changed. Their elements – the social institutes, social groups and individuals appear in intermediate and transitional situations. In a sense, anomie becomes one of the main characteristics of marginality in transforming societies. Դժվար է պատկերացնել որևէ սոցիալական միջավայր առանց մարգինալ երևույթների, առանց մարգինալ խմբերի և մարգինալ մարդկանց, առանց մարգինալ սոցիալական դերերի, մարգինալ գիտակցության և վարքի դրսևորման: Յուրաքանչյուր հասարակությունում անհատները, սոցիալական, էթնիկ խմբերը և սոցիալական շերտերը կարող են հանդես գալ որպես մարգինալ որակների կրողներ: Այլ կերպ ասած, մարգինալությունը սոցիալ-մշակութային և սոցիալ-հոգեբանական երևույթ է, որը միշտ եղել է տարբեր պատմական հասարակությունների, տարբեր սոցիալական տիպերի անբաժանելի մասը։ Այս առումով հատկապես կարևոր է մարգինալության համատեքստում դիտարկվող անոմիայի ֆենոմենի ուսումնասիրությունը։ Трудно представить любую социальную среду без маргинальных явлений, без маргинальных групп и маргинальных людей, без маргинальных социальных ролей, проявления маргинального сознания и поведения. В каждом обществе носителем маргинальных качеств могут выступать индивиды, социальные и этнические группы и социальные слои. Иными словами, маргинальность – это социокультурный и социально-психологический феномен, который всегда был неделимой частью разных исторических обществ, разных социальных типов.
Keywords: Social and Humanitarian Sciences